Reimagining Early Childhood Education in Southern Africa: Transforming fragmented curriculum through cultural pedagogy - Chikuvadze, Pinias; Kamil, Nurhusna; Makuvire, Claretah (Belantika Pendidikan, 2025)
This review scrutinises the transformation of the fragmented Early Childhood Education (ECE) curriculum in Southern Africa. A systematic review approach guided by the PRISMA framework was employed to cross-examine 48 sources purposively selected from targeted databases (Scopus, Web of Science, DOAJ, AJOL and Scielo, SA). Thematic analysis was employed to identify trends and gaps linked to cultural pedagogy and curriculum transformation in ECE across Southern Africa. Based on the results, it was drawn that Ubuntugogy and chat theory formed the theoretical underpinning of cultural pedagogy in the ECE space. It was also revealed that curriculum fragmentation and pedagogical marginalisation were influenced by the historical, structural, and institutional factors. The results acknowledged the significance of language, storytelling, music, and play in nurturing culturally grounded ECE. In addition, the reviewed sources argued for inclusive curriculum frameworks, integration of cultural pedagogy into ECE policies and a paradigm shift towards child-centred and community-based learning. Lastly, the selected sources emphasised the challenges and opportunities in redefining fragmented ECE curriculum across Southern Africa. Based on the results from the review, it was concluded that cultural pedagogy not only brings back pride to indigenous epistemologies but also transforms ECE as a space for social justice, equity, and identity formation. Hence, the need to reimagine ECE not only as an effective vehicle for sharing learning experiences, but also as a profound reflection of diverse cultural heritage across the region.